2020
DOI: 10.1007/s10899-020-09944-3
|View full text |Cite
|
Sign up to set email alerts
|

Why Some Sports Bettors Think Gambling Addiction Prevented Them from Becoming Winners? A Qualitative Approach to Understanding the Role of Knowledge in Sports Betting Products

Abstract: Why some sports bettors think gambling addiction prevented them from becoming winners? A qualitative approach to understanding the role of knowledge in sports betting products

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Other scholars conceive PIU primarily as an impulse-control disorder, due to being interwoven with significant impulse/inhibitory control deficits (Anderson et al, 2017). At least four different types of digital media applications (i.e., online gaming, online pornography, online gambling, and social media use) have been reported as likely high risk for PIU behaviors (Brand, Rumpf, King, Potenza, & Wegmann, 2020;Taylor & Gavey, 2020;Lopez-Gonzalez, Griffiths, & Estévez, 2020;Sun & Zhang, 2020).…”
Section: Maladaptive Outcomes Related To Digital Media Usementioning
confidence: 99%
“…Other scholars conceive PIU primarily as an impulse-control disorder, due to being interwoven with significant impulse/inhibitory control deficits (Anderson et al, 2017). At least four different types of digital media applications (i.e., online gaming, online pornography, online gambling, and social media use) have been reported as likely high risk for PIU behaviors (Brand, Rumpf, King, Potenza, & Wegmann, 2020;Taylor & Gavey, 2020;Lopez-Gonzalez, Griffiths, & Estévez, 2020;Sun & Zhang, 2020).…”
Section: Maladaptive Outcomes Related To Digital Media Usementioning
confidence: 99%
“…Research has identified an extensive list of gendered advertising themes tailored towards specific (male) populations including friendship, sexulaised images, social status, winning, thrill seeking and risk (Deans et al, 2016a). In addition, Gonzalez-Lopez et al (2018) highlight 'knowledge of sport' as a core feature of sport betting marketing designed to increase illusions of control over gambling outcomes, a belief which gamblers undergoing psychological treatment for gambling disorder find it difficult to reconfigure (Gonzalez et al, 2020). Tellingly, the student-athletes in this study appeared to have largely internalised 'knowing' as a reason to bet on one sport (team or match) over another alongside perceptions that some sports (football) are easier to bet on than others.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative data were collected using a focus group interview method and were organised according to team affiliation (see Table 1). The focus group method has been used widely among gambling researchers (e.g., Gordon et al, 2015;Lamont & Hing, 2019;Lamont & Hing, 2020;Lopez-Gonzalez et al, 2020;McGee, 2020) and was selected in order to stimulate open and exploratory discussions among participants in a setting where they felt encouraged to share their views and experiences with the researcher (Conlin & Sillence, 2021). Focus groups were arranged in-person and were conducted in a relaxed and informal manner to ensure individuals felt comfortable discussing the subject of gambling in front of the researcher and their teammates.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Sports bettors in recovery struggle to understand the role that chance played in their betting history and wonder if they would have become successful bettors had they not lost control due to a gambling disorder (Lopez-Gonzalez et al, 2020). During their treatment, cognitive-behavioural therapy -the 'gold standard' for gambling disorder (Petry, 2016) -tries to restructure gamblers' thoughts about luck and skill, but new sports betting forms put into question some long-held truths such as the house edge (Woolley et al, 2013) and the illusion of control (Langer, 1975).…”
Section: Tipsters Skill and Problem Gamblingmentioning
confidence: 99%